2013
DOI: 10.3928/01477447-20130821-13
|View full text |Cite
|
Sign up to set email alerts
|

Cadaver Training Module for Teaching Thoracic Pedicle Screw Placement to Residents

Abstract: Surgical training using simulators has been shown to be highly effective but is not available for some applications and is too expensive for many programs. The authors piloted a cadaver-based module with the goal of objectively measuring and significantly improving orthopedic residents' surgical skills in placing thoracic pedicle screws, an advanced procedure. An experienced spine surgeon placed thoracic pedicle screws in 7 cadavers (T1-T12) to establish the skilled accuracy rate. For this pilot study, 3 ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…[10][11][12] Human cadaver models are also used for practicing both intracranial and spinal surgical techniques. 13 Although these models provide good anatomical detail, limitations include inability to replicate the various neurosurgical pathologies and to reproduce the behavior of living tissue. As a result, alternative training apparatuses have been sought and several studies have explored the use of either synthetic physical or computer-based models for learning neurosurgical spine procedures involving both open and minimally invasive pedicle screw placement and cervical laminectomy or foraminotomy.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Human cadaver models are also used for practicing both intracranial and spinal surgical techniques. 13 Although these models provide good anatomical detail, limitations include inability to replicate the various neurosurgical pathologies and to reproduce the behavior of living tissue. As a result, alternative training apparatuses have been sought and several studies have explored the use of either synthetic physical or computer-based models for learning neurosurgical spine procedures involving both open and minimally invasive pedicle screw placement and cervical laminectomy or foraminotomy.…”
Section: Introductionmentioning
confidence: 99%
“…9,14 A number of recent studies have attempted to compare the benefits of various laboratorybased techniques, although most do not demonstrate significant benefit. 7,9,14 To date, a definitive, evidence-based, laboratory training module has not been delineated.…”
mentioning
confidence: 99%
“…Fifty‐one studies were included in the review, of which 47 were full‐text original research articles and four were conference posters. The main characteristics of studies, including OCEBM and mean MERSQI scores are shown in Tables S2 – S5 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Various score‐based methods were also used, including procedure scores, global rating scale (GRS), OSATS (Objective Structured Assessment of Technical Skills in Surgery) and the GOALS (Global Operative Assessment of Laparoscopic Skills) scale. Seven of the 23 studies were RCTs and 16 were cohort studies. Of the seven RCTs, three compared cadaveric simulation with no simulation training, and four compared cadaveric simulation with low‐fidelity simulation.…”
Section: Resultsmentioning
confidence: 99%